Differential Effects of Dengue Virus on Infected and Bystander Dendritic Cells - Palmer, Dupeh R. (American Society for Microbiology, 2005)
Dendritic cells (DCs) play a central role as major targets of dengue virus (DV) infections and initiators of antiviral immune responses. Previous observations showed that DCs are activated by infection, presumably acquiring the capacity to promote cell-mediated immunity. However, separate evaluations of the maturation profiles of infected and uninfected bystander cells show that infection impairs the ability of DCs to upregulate cell surface expression of costimulatory, maturation, and major histocompatibility complex molecules, resulting in reduced T-cell stimulatory capacity. Infected DCs failed to respond to tumor necrosis factor alpha as an additional maturation stimulus and were apoptotic. Interleukin 10 (IL-10) was detected in supernatants from cultures of DV-infected DCs and cocultures of DCs and T cells. Taken together, these results constitute an immune evasion strategy used by DV that directly impairs antigen-presenting cell function by maturation blockade and induction of apoptosis.